2016
DOI: 10.15671/hjbc.20164418125
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Properties of Nannospalax (Rodentia: Spalacidae) Distributed in North-Iraq

Abstract: K uzey Irak bölgesinden 3 farklı lokaliteden toplanan 11 Kör Fare (Nannospalax) örneği üzerinde ayrıntılı olarak morfolojik özellikleri çalışılmıştır. Bazı taksonomik özellikleri, dış vücut ve baş iskeleti ölçüleri araştırılmıştır. Örneklerden elde edilen bilgiler literatür bilgileriyle karşılaştırılmıştır. Sonuçlar bu bölge Körfare'lerinin incelenen populasyonlarının benzer morfolojik özelliklere sahip olduklarını göstermektedir. Böylece, Kuzey Irak populasyonları morfolojik bakımından Nannospalax ehrenbergi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The Palestinian blind mole-rat (Nannospalax ehrenbergi) could be distinguished from the greater blind mole-rat (Nannospalax microphthalmus) and the lesser mole-rat (Nannospalax leucodon) by the height of the alveolar process, which did not reach the height of the condylar process of the mandibula (5). Coşkun et al (2) found that the molars of North-Iraqi Nannospalax have three roots on all specimens, but roots of M 3 are welded in older specimens; this was also observed in Nannospalax leucodon of our study. Also, the gnathic process has not been previously described in blind molerats, and this is the first paper that described and labeled it.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The Palestinian blind mole-rat (Nannospalax ehrenbergi) could be distinguished from the greater blind mole-rat (Nannospalax microphthalmus) and the lesser mole-rat (Nannospalax leucodon) by the height of the alveolar process, which did not reach the height of the condylar process of the mandibula (5). Coşkun et al (2) found that the molars of North-Iraqi Nannospalax have three roots on all specimens, but roots of M 3 are welded in older specimens; this was also observed in Nannospalax leucodon of our study. Also, the gnathic process has not been previously described in blind molerats, and this is the first paper that described and labeled it.…”
Section: Discussionsupporting
confidence: 82%
“…We compared the results of the previously published studies and found many similarities between Nannospalax leucodon in Bosnia and Herzegovina, Nannospalax ehrenbergi in North Iraq (2), and Nannospalax nehringi (3,4) from Eastern Anatolia. Also, we found similarities with the skull morphology of the Brazilian shrew mouse Blarinomys breviceps (11), which helped us to identify and recognize bones that have not been identified in Nannospalax species yet.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…(1) Hazar Mard Caves (Bate 1930); (2) Ser Amadia, (3) Tinn (Harrison 1956a); (4) Jarmo, (5) Chemchamal Valley (Reed 1958); ( 6) Sersink (Hubbard 1955, Hatt 1959); ( 7) Penjwin (Petter 1961); Jarmo, (8) Palegawra Cave (Turnbull & Reed 1974); ( 9) 22 km southwest of Mosul, (10) Al-Jurn (Coşkun et al 2012(Coşkun et al , 2016; Al-Jurn, (11) Shwan, ( 12) Mughagh (Coşkun et al 2014); Shwan, Mughagh, (13) Bardarash, ( 14 A species restricted to the mountainous northwestern part of Iraq (Fig. 8).…”
Section: S P a L A C I D A Ementioning
confidence: 99%